Evaluating a gender-specific intensive intervention programme: Young women's voices and experiences. (October 2018) - Warwick-Booth, Louise; Cross, Ruth
Background: Disadvantaged young women in England have been documented as having unmet needs. This has resulted in the growth of gender-specific intensive intervention programmes in which a more holistic women-centred service approach is implemented. Gender matters because structural inequalities (bias and disadvantaging societal conditions) that girls are born with influence health, their outcomes and associated inequalities. Aims and objectives: Policy-makers frequently call for the outcomes of intervention programmes to be quantified, and while this is important, it can miss opportunities for critical insights into the subjective experiences of participants as well as the context and circumstances within which change occurs. Methods: This paper reports on evaluation findings from a prototype project (The Way Forward) with a focus on holistic improvement using gender-specific methods and approaches to promote health for disadvantaged young women in a community setting. Findings: This paper documents the voices of young women within the project, illustrated through their creation of storyboards within focus group discussions and interview data from their support workers. Findings highlight the importance of the relational dimension of one-to-one support in achieving positive change in the lives of young women, as well as the complexity associated with efforts to improve their health.